2020
DOI: 10.22207/jpam.14.1.68
|View full text |Cite
|
Sign up to set email alerts
|

A GC-MS Based Metabolic Profiling of Probiotic Lactic Acid Bacteria Isolated from Traditional Food Products

Abstract: A GC-MS based metabolic profiling was carried out to study metabolic differences of lactic acid bacteria isolated from different food sources. Metabolic fingerprinting is a non-targeted procedure where all detectable peaks are considered to establish sample classification. A total of 40 compounds were identified as major metabolites contributing to the difference among five different probiotic lactic acid bacteria. Some of the metabolites identified in this study have been reported as a defrosting agent, antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…Probiotics produce metabolites that have antimicrobial, antimutagenic, and anticarcinogenic activities. These properties can help eliminate gastrointestinal-related diseases ( Bedada et al, 2020 ; Chaudhary et al, 2020 ). B. paranthracis strain MHSD3 has shown to be rich in a variety of secondary metabolites, especially antibacterial and antimicrobial compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Probiotics produce metabolites that have antimicrobial, antimutagenic, and anticarcinogenic activities. These properties can help eliminate gastrointestinal-related diseases ( Bedada et al, 2020 ; Chaudhary et al, 2020 ). B. paranthracis strain MHSD3 has shown to be rich in a variety of secondary metabolites, especially antibacterial and antimicrobial compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Chaudhary, Verma, and Saharan (2020) found that some common compounds from the culture supernatants of Lactobacillus and Pediococcus strains were decane; benzaldehyde, 2,4, dimethyl; dodecane; phenol, 2,4 bis (1,1 dimethylethyl); pyrrolo [1,2a] pyrazine 1,4 dione, hexahydro 3 (2 methylpropyl); n‐hexadeconic acid and benzoic acid. In the current study, although both lactobacilli metabolites were generally different, four compounds such as acetic acid; pyrrolo[1,2‐a]pyrazine‐1,4‐dione, hexahydro‐3‐(phenylmethyl); 2,3,4‐trihydroxybenzaldehyde and 9‐octadecenoic acid were only similar.…”
Section: Resultsmentioning
confidence: 99%
“…Lactobacillus is a gram-positive facultative anaerobic bacterium found widely in fermented food products and can be investigated for the metabolites present in them by based -MS -GC metabolic profiling (Chaudhary et al, 2020). Several microbial species of LAB establish themselves from mouth and gut to large intestine of human beings and thus serve as potential mucosal vaccines (Elagöz et al,1996).…”
Section: Introductionmentioning
confidence: 99%
“…These metabolic profiles GC-MS has consistently been the most favored analytical technique for the analysis of metabolites present in distinct biological samples. Gas chromatography and mass spectrophotometry (GC-MS) present the high chromatographic resolution ascribed to the high sensitivity and specificity of mass spectrophotometry (Chaudhary et al, 2020). In comparison with other techniques, GC-MS can produce a comparably high reproducibility, high resolution, high-quality sensitivity, and goodthroughput analysis, which can be used for analyzing the metabolic products, inclusive of carbohydrates, fatty acids, organic acids, and amino acids (Park et al, 2016).…”
Section: Introductionmentioning
confidence: 99%